Reduction of class I histone deacetylases ameliorates ER-mitochondria cross-talk in Alzheimer's disease - Marinho, Daniela (2023)
Several molecular mechanisms have been described in Alzheimer's disease (AD), including repressed gene transcription and mitochondrial and endoplasmic reticulum (ER) dysfunction. In this study, we evaluate the potential efficacy of transcriptional modifications exerted by inhibition or knockdown of class I histone deacetylases (HDACs) in ameliorating ER-mitochondria cross-talk in AD models. Data show increased HDAC3 protein levels and decreased acetyl-H3 in AD human cortex, and increased HDAC2-3 in MCI peripheral human cells, HT22 mouse hippocampal cells exposed to Aβ1-42 oligomers (AβO) and APP/PS1 mouse hippocampus. Tacedinaline (Tac, a selective class I HDAC inhibitor) counteracted the increase in ER-Ca2+ retention and mitochondrial Ca2+ accumulation, mitochondrial depolarization and impaired ER-mitochondria cross-talk, as observed in 3xTg-AD mouse hippocampal neurons and AβO-exposed HT22 cells. We further demonstrated diminished mRNA levels of proteins involved in mitochondrial-associated ER membranes (MAM) in cells exposed to AβO upon Tac treatment, along with reduction in ER-mitochondria contacts (MERCS) length. HDAC2 silencing reduced ER-mitochondria Ca2+ transfer and mitochondrial Ca2+ retention, while knockdown of HDAC3 decreased ER-Ca2+ accumulation in AβO-treated cells. APP/PS1 mice treated with Tac (30 mg/kg/day) also showed regulation of mRNA levels of MAM-related proteins, and reduced Aβ levels. These data demonstrate that Tac normalizes Ca2+ signaling between mitochondria and ER, involving the tethering between the two organelles in AD hippocampal neural cells. Tac-mediated AD amelioration occurs through the regulation of protein expression at MAM, as observed in AD cells and animal models. Data support transcriptional regulation of ER-mitochondria communication as a promising target for innovative therapeutics in AD.